Tree-Ring Width And Its Interrelation With Environmental Parameters: Case Study In Central Hungary - Ladányi, Zsuzsanna; Blanka, Viktória (Journal of Environmental Geography, 2015)
Tree ring width is influenced by several internal and external factors, among which climate became one of the most dominant due to the altering conditions and patterns of precipitation and temperature. The study aims to analyse the interrelationship between tree ring-width and the dominant environmental parameters in a landscape exposed to water scarcity in the past decades due to climate change and human interventions. Scots pine (Pinus sylvestris), black locust (Robinia pseudoacacia) and white poplar (Populus alba) plantations were sampled to reveal their exposure to climatic forcing and water scarcity (different water availability). Correlation and similarity analysis were carried out to compare the calculated ring-width indices to climatic parameters and aridity indices. Tree ring sensitivity was assessed to reveal the impact of water scarcity on yearly ring-growth. Spatial overlapping of significance levels and mean sensitivity with the hydrological changes of the past decades were evaluated to reveal presumable spatial differences of the investigated samples. In the study area (South Danube-Tisza Interfluve) droughts and the deep groundwater table had both impacts on tree growth. The spectacular decrease of ring-width corresponds to the drought years determined by the investigated aridity indices. The relationship between the climate parameters and the ring-widths varies spatially with the changing site conditions. The highest level of correlation coefficients was experienced in areas with the lowest level of water availability. Ring-width sensitivity assessments showed an increasing tendency of sensitivity when comparing the consecutive decades, except for samples with favorable water availability.